The sleepover secret - Katschke, Judy.; Copyright Paperback Collection (Library of Congress) (New York : HarperEntertainment, 1999)
Ashley is surprised when Mary-Kate reveals a secret.
"A Parachute Press book."
"Based on the hit ABC TV series, starring Mary-Kate & Ashley!"--cover.
Keywords: Twins; Twins